Perlindungan Konsumen Terkait Penentuan Nilai Pajak karena Kesalahan Penginputan Nilai Barang oleh Perusahaan Jasa Titipan Perspektif Maslahah - Sakinah; Uswatun Hasanah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Errors in inputting tax values by consignment service companies have a significant impact on importers as consumers. This study aims to examine the calculation of import tax values, then the impact of errors in inputting tax values on consumers and consumer protection from a maslahah perspective. The research methodology conducted by the author is a type of normative legal research. The approaches used are the statute approach and the conceptual approach. By using primary data sources that involve a review of all relevant regulations and customs or customs tax bill notification letters to importers. Secondary data is obtained from documents, books, articles, and others. The results of the study indicate that the correct import tax value depends on the time of inputting the value of the goods, errors in inputting the value can lead to inaccurate tax calculations, which in turn can harm both consumers and the state. From a maslahah perspective, consumer protection emphasizes justice and public welfare, as well as avoiding transactions that are detrimental and the need for responsibility if any party is harmed. This study emphasizes the importance of accuracy when inputting the value of goods to avoid errors when calculating tax rates.